Enrofloxacin/florfenicol loaded cyclodextrin metal-organic-framework for drug delivery and controlled release - Yucai Wei; Chaoxi Chen; Shuo Zhai; Min Tan; Juebo Zhao; Xiaowen Zhu; Lu Wang; Qun Liu; Tao Dai (Taylor & Francis Group, 2021)
We presented an antibiotic-loaded γ-cyclodextrin metal-organic framework that delivered antibiotics suitable for the treatment of bacterial infections. The γ-cyclodextrin metal-organic framework was developed using γ-cyclodextrin and potassium ion via the ultrasonic method. The antibiotic (florfenicol and enrofloxacin) was primarily encapsulated into the pore structures of γ-CD-MOF, which allowed the sustained release of antibiotics over an extended period of time in vitro and in vivo. Notably, antibiotics-loaded γ-CD-MOF showed much superior activity against bacteria than free antibiotics (lower MIC value) and displayed better long-lasting activity (longer antibacterial time). The antibiotics-loaded γ-CD-MOF showed nontoxic and perfect biocompatibility to mammalian cells and tissues both in vitro and in vivo. These materials thus represent a novel drug-delivery device suitable for antibiotic therapy. This research is of great significance for reducing the generation of bacterial resistance and providing new ideas for the application of γ-CD-MOF.